SOSHCo in UiTM Pahang: Duty, relevance and direction / Rosmi Yuhasni Mohamed Yusuf and Wan Ramlee Wan A. Kadir - Mohamed Yusuf, Rosmi Yuhasni; Wan A. Kadir, Wan Ramlee (2005)
All institutions of higher learning in Malaysia in many ways are undeniably intersected with the potential legal liabilities. No person who are directly connected with a higher education institution, whether student, staff or visitor is, outside the influence of tort and statutory law. Highway correlated with these legal liabilities are the potential hazards. UiTM Pahang, like other higher learning institutions, are highway exposed to numerous potential hazards. These hazards can be reduced or at least contained in many ways with or without incurring costs. The Sub Occupational Safety and Health Committee or SOSHCo is a committee formed to manage the risk of safety and health as a result of the requirement from the Occupational Safety and Health Committee, Shah Alam in their meeting dated July 13th 2004. The idea to form the SOSHCo committee was initiated from there and now this committee is needed in every department, faculty and the branch campus. This article examines and higlights the potential ambit of liability faced by UiTM Pahang and the roles played by the SOSHCo committee with reference to several aspects, including amongst others, the availability of the risk control incentives.